Navigating Earth’s biogeochemical dynamics: Integrating elemental cycles, anthropogenic pressures and planetary boundaries - Slaveykova, Vera I. (Frontiers in Environmental Science, 2025)
Anthropogenic activities increasingly alter Earth’s biogeochemical cycles, threatening the integrity and resilience of critical planetary systems. This perspective paper highlights the pivotal role of biogeochemical cycles in global sustainability challenges such as climate change, biodiversity loss, land degradation, and water scarcity, underlining feedbacks that exacerbate ecosystem degradation and diminish Earth’s self-regulating capacity. Advances in integrated Earth system models demonstrate the necessity of capturing nutrient interactions to accurately predict ecosystem productivity and carbon sequestration, particularly under nutrient-limited conditions. The emergence of novel entities introduces unprecedented vulnerabilities to elemental cycles, with their long-term impacts and planetary boundary exceedances still poorly understood. These challenges, coupled with nutrient boundary exceeding and ongoing climate change, regional variability and nonlinear and cascading responses emphasize an urgent need for interdisciplinary research, enhanced monitoring, and robust regulatory frameworks, supported by advances in modeling, big data analytics, and artificial intelligence.